An exploration of why qualified mental health nurse prescribers do not prescribe. (2nd February 2019) - Oldknow, Helen; Gillibrand, Warren; Clifton, Andrew
Abstract : This article is an exploratory study of perceptions in mental health nurses who are qualified to prescribe yet choose not to do so. In-depth semi-structured face-to-face interviews, field notes and analysis of documents were used to investigate the perceptions of the non–prescribing nurse prescriber. A mapping exercise was conducted to identify potential participants. Interview data analysis was based on the principles of descriptive phenomenology and the research was theoretically framed within concepts of power, structure/agency and culture. This study has contributed to understanding the views of non-prescribing mental health nurse prescribers on why they do not use their prescribing qualification. The findings from this study suggest that there are complex, interlocking factors: power and knowledge; culture; and structure and agency, which may enable or prevent mental health nurse prescribers from independently prescribing.